Benign postinfection polymyositis. Issue 6147 (4th November 1978) - Schwartz, M S; Swash, M; Gross, M
Abstract : Six patients developed persistent muscular cramps, aching pain, and fatigability after an influenza-like illness. Electromyography showed myopathic changes, although results of routine laboratory investigations were normal in all but one patient, whose serum creatine kinase concentration was slightly increased. All but one of the patients improved: three were asymptomatic within one to two years. The syndrome was probably a benign form of polymyositis.